INTRINSIC ELEMENTS OF AROMA KARSA (JOSAR (Journal of Students Academic Research), 2019)
Aroma karsa is such a cool novel by Dee lestari, the fictional novel that carries the smell. It is an interesting novel, there are several elements of the story such as adventure, mystery, romance, family and ancient legend. The researchers are very curious with this novel, we decided to identify this novel as our assignment in literature class, we looked for the references from the book or on the internet to made some summary or looked for the problems which would be interesting to write in this paper.The research was using method qualitative research, the location of the research was in Public Library in Blitar city, the method to collect the data is by reading the novel and looking for the reviewers about Aroma karsa on Internet.The result of research is the researchers can make a review and critics about the novel, fter enjoying Aroma Karsa the blueprint of this manuscript is divided into two stories, namely the world of reality and magic. Reality is the story where Jati and Suma meet who deliver them to the PuspaKarsa expedition and meet NurdinSuroso, Khalil Batarfi, AnungLinglung, YustinusHerlambang, IwanSatyana, JindraMahameru, and AryaJayadi.Furthermore, magic is a story where they must find the village of Dwarapala which is mysteriously located on Mount Lawu and only the aroma can open the way to the village. That's where the epic story takes place when the mystery of the PuspaKarsa is gradually revealed and leads them to an adventure with EmpuSmarakandi, Pucang, Sinom, and ElarManyura